Improvement the Photo Catalytic Properties of ZnS nanoparticle with Loaded Manganese and Chromium by Co-Precipitation Method - Luma Majeed Ahmed (Journal of Global Pharma Technology, 2018)
This work aims to study the photocatalytic decolorization of Reactive black 5 as the commercial azo reactive dye was studied with a presence prepared ZnS nanopowder and metalized by manganese and chromium (1:1)%. These prepared catalysts were have been made by using a co-precipitation method. The characteristics of prepared samples were investigated by X-ray diffraction(XRD), AFM and fluorescence spectrometry, XRD data were helpful to calculate the mean crystal size by the using Scherrer equation , the mean crystal size for prepared bare ZnS is more value compared with that value for prepared Mn: ZnS: Cr and equal to19.986 and 17.114 respectively. The AFM images explained that the shapes for prepared samples are semispherical and the number of particle sizes of them that equal to 93.740, 51.020 for bare ZnS and metalized (Mn, Cr) ZnS respectively. The Crystallinty index was calculated by depending on particle sizes attained from AFM and mean crystallite sizes obtained from XRD and results indicated to the particle sizes for them contain (5-3) crystals. The results of measured Bg of prepared samples were obtained, that the Bg of prepared ZnS was a small value (3.558 eV) at λ max =348.5while the Bg of metalized ZnS was (3.568 eV) at λ max =347.5. Atomic absorption spectrometry was used to ensure if all the loaded amounts from Mn: Cr were completed that, so, the loaded process is successful. The effect of temperature was estimated the calculated activation energies for prepared ZnS and prepared Mn: ZnS: Cr ( 14 âˆ†Ea=20.760 kJmole